The Influence of Financial Self-Efficacy, Risk Perception, and Herding on Gold Investment Decisions among Generation Z in Bandung City - Silvi Febriani; Vidya Ramadhan Putra Pratama (Escalate : Economics and Business Journal, 2026)
The rapid growth of digital gold investment has increased Generation Z's participation in investment activities, yet inconsistent findings in previous studies leave the psychological factors driving their investment decisions unclear. This study addresses this gap by examining the influence of Financial Self-Efficacy, Risk Perception, and Herding on gold investment decisions among Generation Z in Bandung City. A quantitative, explanatory cross-sectional survey was employed, collecting data from 137 respondents selected through purposive sampling using a five-point Likert-scale questionnaire. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4, while IBM SPSS Statistics was used as a complementary tool to perform a simultaneous F-test. The results show that Financial Self-Efficacy, Risk Perception, and Herding each have a positive and significant influence on gold investment decisions, with Herding being the strongest predictor. The simultaneous F-test confirms that the three variables jointly have a significant effect, together explaining 59.1% of the variation in gold investment decisions. These findings indicate that gold investment decisions among Generation Z result from a combination of individual psychological factors and social interactions within the digital investment environment, highlighting the importance of strengthening financial capabilities and providing credible investment information to encourage more rational investment decisions.